Successful Management of Dentin Hypersensitivity: A Narrative Review - Rosmaliza Ramli; Nurhafizah Ghani; Haslina Taib; Nor Haliza Mat-Baharin (Wroclaw Medical University, 2024)
Indexed by WOS/ Scopus